Modelagem para a mensuração do desempenho de linhas de produção para indústrias frigoríficas - Hupfer, Naiara Tatiane (2015)
measuring their performance possible, these days, to get a more accurate reflection of reality found in relation to the environment in which it is inserted. Against this backdrop, this paper aims to propose a model for measuring the performance of production lines for beef slaughterhouses in order to make it possible to obtain greater insight into the main characteristics that affect the performance of the productive process lines a vital sector for the country's economy, because it is a staple food in the diet of Brazilians and also as export to various countries. Therefore, it was necessary to build a model based on the identification of Key Performance Indicators (KPI) directly linked to the objective indicator that is the situation of production lines in relation to the context. For the model test was proposed to use in a company's refrigerator industry, located in southern Brazil during the months of March to June 2014, at test end was obtained as a result the individual performance of each KPI analysis, as well as the overall performance of the production line, noting that this production line needs adjustments to achieve the expected result and found satisfactory for the company.